A Half-Century Assessment of the Study of Culture and Emotion. (August 2022) - Matsumoto, David; Wilson, Matthew
Research on emotion and affective sciences is flourishing today like never before. The impetus for this surge is largely rooted in studies of emotion across cultures and coincides with the half century existence of the International Association for Cross-Cultural Psychology (IACCP). Beginning with studies initially documenting the universality of the expression and recognition of certain facial expressions of emotion in the 1970s, cross-cultural research was crucial in providing further evidence for the universality of antecedents, appraisals, subjective experiences, self-reported responses, and physiological reactions throughout the 1980s and 1990s. That same literature also demonstrated the existence of many cultural variations in these emotion domains, as well as in the concepts, language, attitudes, beliefs, and values about emotion. We review this literature with the goal of demonstrating some of the many meaningful and important contributions IACCP and cross-cultural studies have made to the field of emotion and affective sciences. This area of research has also been marred by considerable controversies for almost the entire period of study, and we describe those as well. We conclude with a presentation of current models of understanding the association between culture and emotion that integrate disparate cross-cultural findings and address controversies in the field, in the hope that such models can serve as a platform for renewed cross-cultural research in this area for the next half century and beyond.